Innovation in Cyber Public Relations at Grand Soll Marina Hotel - Astika Puspita Sari; Lathifa Prima Ghanistyana; Mujahid Muhammad Ihsan; Suci Nurfadilah; Yoris deriyana (International Journal Labs, 2025)
Public relations has undergone a major transformation in the digital era, with the rise of cyber public relations strategies that leverage online platforms to strengthen brand presence and customer engagement. This study focuses on identifying and analyzing the innovations in cyber public relations implemented by Grand Soll Marina Hotel. The main objective is to examine how digital communication strategies, such as the use of social media, website optimization, and influencer collaboration, contribute to the hotel’s public image and customer loyalty. This research adopts a qualitative descriptive approach through in-depth interviews with the hotel’s PR team, content analysis of digital platforms, and documentation studies. The findings reveal that Grand Soll Marina Hotel applies innovative cyber PR practices, including interactive Instagram content, integrated booking services via social media, and real-time customer feedback responses. These innovations not only enhance the hotel’s brand reputation but also create a more personalized and responsive relationship with its target audiences. The managerial implication suggests that continuous adaptation to digital trends is essential for the sustainability of PR strategies in the hospitality industry.